1997
DOI: 10.1007/bf00119855
|View full text |Cite
|
Sign up to set email alerts
|

Uranium(6+) sorption on montmorillonite: Experimental and surface complexation modeling study

Abstract: Sorption interactions with montmorillonite and other clay minerals in soils, sediments, and rocks are potentially important mechanisms for attenuating the mobility of U(6+) and other radionuclides through the subsurface environment. Batch experiments were conducted (in equilibrium with atmospheric Pco2) to determine the effects of varying pH (2 to 9), solid-mass to solution-volume ratio (M/V = 0.028 to 3.2 g/L), and solution concentration (2 x 10 -7 and 2 x 10 -6 M 233U) on U(6+) sorption on SAz-1 montmorillon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
69
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 33 publications
(56 reference statements)
9
69
0
1
Order By: Relevance
“…For all kinds of bentonite, with the exception of H-bentonite, the desorption isotherms differed from the sorption isotherms, which attested to the irreversibility of the entire sorption process. Surface precipitation and surface complexation play important roles in U(VI) immobilization by bentonite [26][27][28].…”
Section: Resultsmentioning
confidence: 99%
“…For all kinds of bentonite, with the exception of H-bentonite, the desorption isotherms differed from the sorption isotherms, which attested to the irreversibility of the entire sorption process. Surface precipitation and surface complexation play important roles in U(VI) immobilization by bentonite [26][27][28].…”
Section: Resultsmentioning
confidence: 99%
“…However, these previous studies did not consider the potential formation of uranyl-carbonate ternary surface complexes on clay surfaces because their experiments were performed either under CO 2 (g) free or low CO 2 (g) conditions. 5,29,30,32 Recently, more detailed studies by Catalano and Brown Jr. 33 and Arai et al 34 using EXAFS spectroscopy revealed that U(VI) adsorption onto montmorillonite and imogolite surfaces occurs as uranyl-carbonate ternary surface complexes in systems equilibrated with atmospheric CO 2 . Formation of polymeric surface complexes via adsorption of aqueous UO 2 ) 3 (OH) 5 + was not observed, which is consistent with our calculation that at low U(VI) concentration (≤1 μM) and in the presence of atmospheric CO 2 , the formation of aqueous UO 2 ) 3 (OH) 5 + is not favored (Figure S1 in SI).…”
Section: +mentioning
confidence: 99%
“…At pH and carbonate concentrations typical of natural waters, sorption of U(6+) on montmorillonite can vary by four orders of magnitude and can become negligible at high pH. A Diffuse-Layer model (DLM) assuming aluminol (>AlOH ∘ ) and silanol (>SiOH ∘ ) edge sites and two U(6+) surface complexation reactions per site effectively simulates the complex sorption behavior observed in the U(6+)-H 2 O-CO 2 -montmorillonite system at an ionic strength of 0.1 M and pH > 3 5 [7].…”
Section: Introductionmentioning
confidence: 99%